The Kansas PEAK 2.0 Program Facilitates the Diffusion of Culture-Change Innovation to Unlikely Adopters. (13th February 2017) - Hermer, Linda; Cornelison, Laci; Kaup, Migette L; Poey, Judith L; Stone, Robyn; Doll, Gayle
Abstract: Purpose of the Study: Recent studies have shown that nursing homes adopting culture change are disproportionately not-for-profit and CCRC-affiliated, with greater quality of care. Through the lens of diffusion-of-innovation theory, we examined whether Kansas' Medicaid pay-for-performance program PEAK 2.0, which incents the adoption of person-centered care (PCC) and worker empowerment, succeeded in its goal of spreading adoption to atypical- as well as typical-adopting nursing homes. Design and Methods: We conducted a retrospective cohort study of 349 nursing homes in the state during PEAK 2.0's existence, 2012–2016. We constructed a data set combining state program data, provider characteristics from CMS data sets, and other demographic information from the 2010 Census. With a series of logistic regression models, we tested whether program joiners differed from nonjoiners by profit status and other demographic factors, as well as quality-related and case-mix factors. Results: We found that in PEAK 2.0's first year, 2012, adopters were more likely to be not-for-profit and part of a CCRC, with higher occupancy rates and greater quality. However, by 2013 these associations became marginal, and in 2014 and 2015, we found no differences between program joiners and nonjoiners. Implications: The results show that by PEAK 2.0's third year, the program—with its large financial incentive and other potentially important characteristics—succeeded in attracting a large set of nursing homes whose demographics were representative of those in the state. This is important because other studies have found that the adoption of PCC is associated with improved health and well-being for residents.